Stigma, discrimination, violence, and HIV testing among men who have sex with men in four major cities in Ghana. Issue 8 (2nd August 2020) - Gyamerah, Akua O.; Taylor, Kelly D.; Atuahene, Kyeremeh; Anarfi, John K.; Fletcher, Michelle; Raymond, Henry F.; McFarland, Willi; Dodoo, F. Nii-Amoo
ABSTRACT: LGBTQ populations experience human rights abuses worldwide; data need to document the health impact of these experiences in Africa. In Ghana, we measured events of sexuality-based stigma, discrimination, and violence among men who have sex with men (MSM) and the impact on HIV testing behavior. Data are from respondent-driven sampling surveillance surveys in Accra/Tema, Kumasi, Cape Coast/Takoradi, and Koforidua. Discrimination was common among MSM: 6.2%–30.6% were refused services, 29.0%–48.9% experienced verbal/symbolic violence, 2.8%–12.8% experienced physical violence, 12.3%-30.0% experienced sexual violence due to their sexuality in the preceding year. MSM who experienced sexual violence in their first male sexual encounter were less likely to ever test for HIV in Accra/Tema and Cape Coast/Takoradi. Further studies are needed to examine the impact of stigma and violence on MSM's HIV health-seeking behavior in Ghana. Structural interventions are needed to mitigate the consequences of stigma and discrimination on MSM health and well-being.